2018
DOI: 10.1007/s00376-018-7267-7
|View full text |Cite
|
Sign up to set email alerts
|

On Northern Hemisphere Wave Patterns Associated with Winter Rainfall Events in China

Abstract: During extended winter (November-April), 43% of the intraseasonal rainfall variability in China is explained by three spatial patterns of temporally coherent rainfall. These patterns were identified with empirical orthogonal teleconnection (EOT) analysis of observed 1982-2007 pentad rainfall anomalies and connected to midlatitude disturbances. However, examination of individual strong EOT events shows that there is substantial inter-event variability in their dynamical evolution, which implies that precursor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These experiments were previously analyzed by Stephan et al (2018b), where more details of the simulations are given. Stephan et al (2018a) showed that these simulations well capture extratropical Rossby wave propagation over Eurasia.…”
Section: Simulationsmentioning
confidence: 75%
“…These experiments were previously analyzed by Stephan et al (2018b), where more details of the simulations are given. Stephan et al (2018a) showed that these simulations well capture extratropical Rossby wave propagation over Eurasia.…”
Section: Simulationsmentioning
confidence: 75%
“…Orthogonal Teleconnections (EOT) has been applied in China (Stephan et al, 2017a(Stephan et al, , 2017b(Stephan et al, , 2018.…”
Section: Analysis Of the Dipole-based Statistical Modelmentioning
confidence: 99%
“…The Silk Road pattern (SRP) is a large-scale summertime teleconnection of the upper-level winds over Europe and Asia (Enomoto et al 2003). It is a manifestation of the Rossby waves that form in the subtropical westerly jet (SWJ), where the SWJ acts as a waveguide due to the meridional change in zonal winds (Hoskins and Karoly 1981, Enomoto et al 2003, Stephan et al 2018. It can be considered as the Asian branch of the circumglobal teleconnection (Ding and Wang 2005).…”
Section: Introductionmentioning
confidence: 99%